TRADITIONAL FASHION INDUSTRY AND JUKUN CULTURE, NORTH CENTRAL NIGERIA - Bello Zakariya Abubakar; Hamisu Sani Ali (International Studies Journal)
This is an enterprise devoted to the business of making and selling of clothes among the Jukun and Abakwariga in North Central Nigeria. The traditional fashion industry is cottage industry not modern fashion industry and it forms part of larger social and cultural phenomenon known as Kyadzwe. It is a concept that embraces not only the fashion business but arts and craft of fashion. It involves not only production (Weaving, dyeing and beating) but also selling and wearing. The industry distinguishes between the fashions of AkuUka and other notable as well as ordinary people.In other words, the colour for Aku is quite different from the colour of ordinary people. Fashon is simply defined as the styles of clothing and accessories worn at any given time by group of people that is Jukun and Abakwariga. Thus, every ethnic or religious group has their peculiar cultural clothes which are symbols of their cultural heritage. In the case of Jukun people of Central Nigeria, they are known for their “Akya” wrapper clothes which are confined to them alone. Therefore, the fundamental concern of this paper is the methods and processes involved in the production of Jukun “Adire” clothes so to speak; Challenges in the production and marketing. Then, finally, the paper focuses on the cultural, political and economic importance of “Adire” cloth to the Jukun and Abakwariga.